A COMPARATIVE STUDY OF FOCUS HARMONIC SCALPEL VERSUS CONVENTIONAL VASCULAR LIGATURE TECHNIQUE IN PATIENTS UNDERGOING TOTAL THYROIDECTOMY - Bangash, Imran Ullah Khan; Akhtar, Muhammad Saeed; Bibi, Nadia; Haider, Rehan; Safdar, Kamran; Gul, Fahad (Journal of Ayub Medical College Abbottabad, 2025)
Background: Thyroid surgery is one of most commonly employed procedures by the surgeons. Evolution of the technique was based on different techniques employed during the dissection of the thyroid tissue, control of bleeding to ensure hemostasis and nerve monitoring with the aim to decrease the complications during the intraoperative and the post operative period. Objective was to compare total thyroidectomy with FOCUS Harmonic scalpel with conventional vascular ligature technique in patients undergoing total thyroidectomy. It was a randomized controlled Trial conducted at the CMH Bahawalpur from 1st July to 31st Dec 2022 (6 Months). Methods: A total number of 78 patients who were planned for total thyroidectomy were included in the trial. Employing a non-probability consecutive sampling technique via lottery method 39 patients were assigned to either of the 02 groups, i.e., Group A (harmonic scalpel technique) and Group B (conventional vascular ligature technique). Recorded variables included mean operative time, intraoperative and postoperative blood loss. Demographic characteristics and ASA grade were recorded for each patient. Results: Mean age of the patients in Group A was 44.05±6.37 years while 44.79±7.62 years in Group B. Male to female ratio was 1:2 among the total participants with 26 (33.3%) males and 52 (66.7%) females however male participants in both groups were 11 (28.2%) versus 15 (38.5%) and females were 28 (71.8%) versus 24 (61.5%) respectively. Harmonic scalpel technique showed significant results in terms of mean operative time, intraoperative and post operative blood loss as compared to conventional vessel ligature technique with a p<0.05. Conclusion: In terms of mean operative time, intraoperative and postoperative blood loss Harmonic scalpel technique is superior to conventional vascular ligature technique for total thyroidectomy.